Nevogenesis : Mechanisms and clinical implications of nevus development - Marghoob, Ashfaq A. (Springer Berlin Heidelberg, 2012)
Paul Gerson Unna's "Abtropfung" theory that nevi develop through migration of nevus cells from the epidermis to the dermis prevailed for almost a century until the "Hochsteigerung" theory postulated the reverse pattern of migration based on newly acquired observations from histopathology and studies of embryogenesis. Most recently, however, new insights gained from epidemiology, cross-sectional and longitudinal studies of nevi, dermoscopy and confocal microscopy, and cellular and molecular studies have brought into question both of the aforementioned theories. This book provides a comprehensive guide to current knowledge about nevogenesis by presenting these latest advances and in addition discusses issues yet to be resolved. It will assist practicing physicians in effectively managing patients with a variety of nevi and will also be of great value to researchers in the field. Importantly, since nevi are associated with an increased risk of melanoma, understanding nevogenesis may help to unravel some of the mysteries of melanomagenesis.